Cover Picture: Tracking Reaction Pathways by a Modular Flow Reactor Coupled to Electrospray Ionization Mass Spectrometry (Chemistry ‐ Methods 10/2021). Issue 10 (24th September 2021) - Tripodi, Guilherme L.; Derks, Max T. G. M.; Rutjes, Floris P. J. T.; Roithová, Jana
Abstract : The Front Cover shows a mini‐plant for automated monitoring of chemical reactions. Flow chemistry enables screening of chemical reactions under well‐defined conditions that can systematically vary. Mass spectrometry couples it with the detection of low abundant reaction intermediates. Therefore, this platform allows tracking reaction pathways, monitoring reaction kinetics of intermediates and is set for a discovery of novel chemical transformations in future. More information can be found in the Full Paper by Guilherme L. Tripodi et al .